Two new species of Deois Fennah, 1949 (Hemiptera: Cercopidae) from Brazil - Carvalho, Gervásio Silva; Teixeira, Juliana Stephanie Galaschi (Zootaxa, 2011)
Two new species of Deois Fennah (Hemiptera: Cercopidae), Deois (Deois) bisignata Carvalho sp. nov. and Deois (Deois) quadrisignata Teixeira sp. nov., are described and illustrated from central Brazil.